Potentially inappropriate drug use in myasthenia gravis: a real-world population-based cohort study in Italy - Crescioli, Giada; Finocchietti, Marco; Paoletti, Olga; Brunori, Paola; Sciancalepore, Francesco; Tuccori, Marco; Addis, Antonio; Vannacci, Alfredo; Lombardi, Niccolò; Kirchmayer, Ursula, The CAESAR study group (Frontiers in Neurology, 2023)
To evaluate the use of pyridostigmine (Py) in presence of contraindications, and the use of concomitant potentially contraindicated drugs in a cohort of patients affected by Myasthenia Gravis (MG) in the Italian Regions of Lazio, Tuscany, and Umbria.Methods: This is a retrospective cohort study. A multivariate logistic regression model was used to evaluate the determinants of pyridostigmine Py and of potentially contraindicated drugs use in MG patients.Results: Among 591 incident pyridostigmine Py users affected by MG, 91 (15.4%) had at least one of the contraindications considered at the first prescription of pyridostigminePy. Patients prescribed with pyridostigmine Py in presence of contraindications were more frequently affected by diabetes, obesity, and renal diseases. Age 75+ years (odds ratio,